Decoding cultural conflicts - Koçak, Özgecan; Puranam, Phanish; Yegin, Afşar (Frontiers in Psychology, 2023)
Conflicts around policy decisions inside and outside organizations can exist even when the incentives of all parties are aligned. These can often be traced to differences in cognitions such as beliefs and values, which are central elements of a culture. However, not all such cultural differences lead to equally serious conflict. We propose that perceived misalignment of either causal or moral codes decreases perceived likelihood of reaching an agreement, increases perception of relationship conflict, increases perceived likelihood of parties avoiding (vs engaging with) each other in the future, and increases perceptions of negative affect developing between the two parties. We also expect that these effects will be stronger when moral codes and not causal codes are misaligned and strongest when both causal and moral codes are misaligned. We test these arguments using vignette-based experimental studies.